The ACE and BDKRB2 gene polymorphisms in Russian athletes - Mustafina, L. J.; Timshina, Y. I.; Astratenkova, I. V.; Ahmetov, I. I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Human physical performance phenotypes are classical quantitative traits influenced by many gene variants and environmental factors. Studies suggest that insertion-deletion (I/D) polymorphisms in ACE and BDKRB2 genes are associated with aerobic capacity and elite endurance athlete status. Angiotensin-converting enzyme (encoded by ACE gene) exerts a tonic regulatory function in circulatory homeostasis, through the synthesis of vasoconstrictor angiotensin II, which also drives aldosterone synthesis, and the degradation of vasodilator kinins. The presence (I allele) rather than the absence (D allele) of a 287 bp Alu-sequence insertion fragment of the ACE gene is associated with lower serum and tissue ACE activity and improved endurance performance (Puthucheary et al. 2011). Bradykinin is a potent endothelium-dependent vasodilator and acts via the bradykinin B2 receptor (encoded by BDKRB2). The absence (-9), rather than the presence (+9), of a 9 bp repeat sequence in exon 1 has previously been shown to be associated with increased gene transcription, higher BDKRB2 mRNA expression and higher efficiency of muscular contraction (Williams et al. 2004). The aim of the study was to investigate ACE and BDKRB2 gene polymorphisms in combination in a large cohort of Russian athletes. Methods: One thousand three hundred and sixty four athletes from 45 sporting disciplines and 507 controls were involved in the study. Genotyping was performed by PCR. To assess the combined impact of 2 gene polymorphisms, all athletes were classified according to the number of `endurance` alleles they possessed. Results: The proportion of subjects with a high (3-4) number of `endurance` alleles was greater but not significantly in endurance-oriented athletes (n=131) compared to controls (34.4 vs 26.8%; P=0.088). The same trend was observed in athletes with mixed endurance/power activity (n=1032; 29.5%, P=0.283) and a whole group of athletes (n=1364; 30.1 vs 26.8%; P=0.162). Conclusion: Thus, we found a trend toward an association between ACE and BDKRB2 polymorphisms and endurance athlete status. Our data suggest that each DNA locus can explain a very small proportion of the phenotypic variance. Therefore, the use of very large sample sizes and the genotyping of many genes are needed to detect associations between gene variants and sport-related phenotypes.